If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(u + 2) + -4u = -24 Reorder the terms: 8(2 + u) + -4u = -24 (2 * 8 + u * 8) + -4u = -24 (16 + 8u) + -4u = -24 Combine like terms: 8u + -4u = 4u 16 + 4u = -24 Solving 16 + 4u = -24 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 4u = -24 + -16 Combine like terms: 16 + -16 = 0 0 + 4u = -24 + -16 4u = -24 + -16 Combine like terms: -24 + -16 = -40 4u = -40 Divide each side by '4'. u = -10 Simplifying u = -10
| X-9=-6+-5 | | -25=4(w-8)+3w | | Y=-0.1(600)+1 | | 9/2x=60 | | 34=8(y+5)-6y | | 0.2x+25=9 | | m^2-10m+10=14 | | [5n+9]+17=4 | | 4x+17=x-19 | | r^3+8=0 | | 7p^2=-6p+3 | | Y=-0.1(45)+1 | | 16a+8b= | | 2x^2-6x+9=340 | | Y=2+4.5x | | -3x^4+16x^3-27x^2=0 | | y=4.5x+2 | | Y=-22.5x-1 | | -c+11=2.4+x | | log(2x)+log(3x)=log(96) | | 9/5(191.8) | | 4y-20x=8 | | (3x-4z)(x-7z)= | | 108x+4=13+46x-2 | | 35=m^2-2m | | -2x^2+8x-7=0 | | (y-7)-y=6 | | 4(v-7)+2v=8 | | 23+3y-2=14y-14-4y | | (3/7)-(x/4)=1/28 | | x-(y-z+2)= | | (2x^2)+16x+22=0 |